PROSEDUR PEMERIKSAAN MRI CERVICAL DENGAN KONTRAS PADA KASUS SPONDILITIS MYELOPATHY - Sofie Nornalita Dewi; Diyah Haryani (JRI (Jurnal Radiografer Indonesia), 2020)
Background: Magnetic Resonance (MRI) examination is one of the best way to diagnose spondylotic disease. It is an invasive imaging that does not use any ionic radiadion and able to visualize spinal cord and subarachnoid space. In order to gain a specific information, there are some modifications made by radiographer in the cervical MRI in the case of myelopathy spondylotic done at RSUD Banyumas. The modifications include choice of sequence, contrast media usage, and coil type usage. The aim of this research is to understand the purpose of those modification that already done in cervical MRI in the case of myelopathy spondylotic doe at RSUD Banyumas. Methods: This study use descriptive qualitative method with a case study approach conducted at RSUD Banyumas. The time of the study was November 2017. The study was conducted on a cervical MRI patient in the case of myelopathy spondylotic. Data collection was carried out by observing and interviewing two radiographers, one radiology specialist at RSUD Banyumas regarding purpose of those modification that already done in cervical MRI in the case of myelopathy spondylotic doe at RSUD Banyumas. The collected datas were arranged to become transcribe and were analyzed to get a discussion and conclusion. Results: Procedure of cervical MRI patient in the case of myelopathy spondylotic at RSUD Banyumas started with patient preparation, including fasting, health history screening, cloth changing and demetalization. Sequences that are used include sagittal and transversal T1WI SE, sagittal, transversal, and coronal T2WI FSE, MR myelography, added by sagittal, transversal, and coronal T1WI SE post contrast media. Carotis coil are used in this examination instead of neck coil. Conclusions: The modification in examination of cervical MRI myelopathy spondylotic patient at RSUD Banyumas is done regarded to radiologist and neurologist request, and also due to patieny condition. All of the sequences that are used have its own purpose which complimen each other, the contrast media used in order to visualize a specific patology.